Ensaios em finanças públicas municipais - Wanderley, Claudio Burian (2009)
This thesis aims to discuss municipal public finance issues. An improvement of the Brazilian fiscal federalism, with greater resources decentralization and the implementation of high-powered rules for the federative transfers may be an important tool in the improvement of our social conditions. To do so, this thesis was divided into four distinct parts. The first chapter discusses the oil revenues impacts on unicipalities’ public finance. The legal changes that occurred in Brazil in the nineties in the oil and gas sector led to increasing royalties transfers to Brazilians states and municipalities. The annedoctical evidence that this transfers are not been used properly - in a way that would increment the local welfare - have originated a important discussion about these distribution rules. This paper tries to identify this revenues impacts over others municipalities’ fiscal variables. It seems that this did not impact the others sources of municipalities revenue. Unhappily, some of the resources (which distribution is either more or less concentrated) led the municipalities to increase their current expenditures and diminishes their investments efforts. At the same time, they are not spending this extra money in a way that would increment the local welfare. On the other hand, the resources which distribution is between these two limits has the opposite effect. The second chapter discusses the impact of oil revenues on the proficiency of fourth grade students of primary public schools. The oil revenues - bundled or not - were not statistically significant in explaining the observed student performance in Portuguese and mathematics. This result, however, must be analyzed with caution, since it is not trivial to identify how (and when) these effects would be generated. However, different sources of municipal revenue would impact differently the students’ proficiency scores, explaining why we need to better understand these differences to design more efficient constitutional transfer mechanisms to the municipalities. In the third chapter, we study the impacts of municipal emancipation occurred in the 90s on the well-being of local populations. More than a thousand of new municipalities were created at the nineties in Brazil, due the new Federal Constitution of 1988. There is anecdotic evidence that this was a pretty harmful process for the Brazilian welfare, but there were no systematic attempt to valuate it properly. This paper tries to do so using data from Minas Gerais municipalities which number has grown from 723 to 853 ones in that decade. The results suggest that this process strongly improved the welfare of the local population. This implies that local political markets are efficient and it should be allowed for any district to emancipate from its former municipalities, if their population wishes to do so. Finally, in the fourth chapter we analyze the impact of law (implemented in Minas Gerais) who sought to increase the incentives pro-efficiency of municipal governments. In order to improve the welfare of its citizens, the state government of Minas Gerais (Brazil) has imposed, at 1995, the state law 12.040, known as Robin Hood law. It stated that 25% of the revenue transferred to the municipalities should be allocated through observable results achieved in education, health, environment among others. In other words, this law established a high power contract between the state government and the municipalities, which is not very usual. This study shows that this law had a significant impact on the municipalities’ education and health. But it’s necessary to redesign these transfers’ rules, in order to improve its power and its results. These results shows that the use of high powered rules in federative transfers could be a strong mechanism in order to improve the population welfare.